Inducing Error Management Culture – Evidence From Experimental Team Studies - Klamar, Alexander; Horvath, Dorothee; Keith, Nina; Frese, Michael (Frontiers in Psychology, 2022)
Field studies indicate that error management culture can be beneficial for organizational performance. The question of whether and how error management culture can be induced remained unanswered. We conducted two experiments with newly formed teams, in which we aimed to induce error management culture and to explore whether we would also find beneficial effects of error management culture on performance in an experimental setting. Furthermore, we tested whether culture strength moderates the relationship between error management culture and performance. In Study 1, we used two tasks that require rational problem solving. In Study 2, we used a task that requires creative problem solving. We successfully manipulated error management culture in terms of an effect on perceived error management culture within the teams. However, in neither of the studies we were able to find a direct effect of error management culture on performance. Also, we did not find culture strength to moderate the error management culture and performance relationship. We discuss potential theoretical and alternative explanations for our results, and provide an outlook for future studies.